Prostate cancer cells enhance interleukin‐15‐mediated expansion of NK cells. (7th August 2019) - Sakellariou, Christina; Elhage, Oussama; Papaevangelou, Efthymia; Giustarini, Giulio; Esteves, Ana M.; Smolarek, Dorota; Smith, Richard A.; Dasgupta, Prokar; Galustian, Christine
Abstract : Objectives: To identify cytokines that can activate and expand NK cells in the presence of prostate cancer cells in order to determine whether these agents may be useful in future intra‐tumoural administration in pre‐clinical and clinical prostate cancer trials. Materials and Methods: Lymphocytes isolated from normal donor blood were set up in co‐cultures with either cancer or non‐cancerous prostate cell lines, together with each of the cytokines interleukin (IL)‐2, IL‐12, IL‐15, interferon (IFN)‐γ or IL‐21 for a period of 7 days. Then, expansion of NK cells, NKT cells and CD8 T cells was measured by flow cytometry and compared with the expansion of the same cells in the absence of prostate cells. The cytotoxic activity of NK cells, as measured by perforin and tumour cell killing, was also assessed. NK cell receptors and their corresponding ligands on prostate tumour cells were analysed to determine whether any of these were modulated by co‐culture. The role of the tumour‐secreted heat shock proteins HSP90 and HSP70 in the expansion of NK cells in the co‐cultures was also investigated because of their effects on NK and CD8 T‐cell activation. Results: We showed that, among a panel of cytokines known to cause NK cell activation and expansion, only IL‐15 could actively induce expansion of NK, NKT and CD8 T cells in the presence of prostate cancer cell lines. Furthermore, the expansion of NK cells was far greater (up to 50% greater) in the presence of the cancer cells (LNCaP, PC3) than when lymphocytes were incubated alone. In contrast, non‐cancerous cell lines (PNT2 and WPMY‐1) did not exert any expansion of NK cells. The cytolytic activity of the NK cells, as measured by perforin, CD107a and killing of tumour cells, was also greatest in co‐cultures with IL‐15. Examination of NK cell receptors shows that NKG2D is upregulated to a greater degree in the presence of prostate cancer cells, compared with the upregulation with IL‐15 in lymphocytes alone. However, blocking of NKG2D does not inhibit the enhanced expansion of NK cells in the presence of tumour cells. Conclusions: Among a panel of NK cell‐activating cytokines, IL‐15 was the only cytokine that could stimulate expansion of NK cells in the presence of prostate cancer cells; therefore IL‐15 may be a good candidate for novel future intra‐tumoural therapy of the disease.